The effect of LMNA mutations on lamin AC and binding partner interactions and cellular distribution - Labib, Sarah (University of Ottawa (Canada), 2011)
Mutations in the LMNA gene, which encodes the nuclear intermediate filament proteins lamin A and lamin C, are associated with over ten tissue-specific diseases, including Dilated Cardiomyopathy (DCM) and lone Atrial Fibrillation (lone AF). There is no clear genotype-phenotype relationship between the location of the mutation and the associated disease phenotype. The general hypothesis of this thesis is that LMNA mutations exert their tissue-specific effects via the perturbation of lamin A and lamin C's specific interacting partners. Protein kinase C alpha, PKCalpha, is a lamin A/C binding partner implicated in heart failure and cardiac hypertrophy. Furthermore, abnormal PKCalpha function results in IKAch activity associated with chronic AF. My first aim is to identify specific phenotypes associated with three laminopathies: lone AF, DCM, and DCM with AF by a) comparing the cellular phenotype induced by LMNA mutations associated with lone AF, DCM, and DCM with AF and b) determining the effect of the mutations on the cellular distribution of PKCalpha. I found two previously unreported mutant lamin A and C phenotypes -- cytoplasmic lamin A/C extrusion and the formation of intranuclear lamin A/C sickle-shaped aggregates associated with one lone AF mutation and one DCM mutation. I show that PKCalpha is mislocalized to the nucleus in C2C12 cells transfected with the same mutants. The E2 conjugating enzyme of the Sumo process, Ubc9, is a reported lamin A/C binding partner. Sumo1 is a post-translational modifying protein that is sequestered within mutant lamin A/C aggregates and has increased substrate conjugation in DCM-associated mutant cells. My second aim is to determine how lamin A and C are involved in the Sumo process by a) investigating Ubc9 cellular distribution and lamin A and C binding in the presence of DCM-associated LMNA mutations and b) determining whether lamin A and/or Care Sumo! binding partners. I show that Ubc9 is mislocalized from the inner nuclear membrane to the mutant lamin A/C aggregates. Co-immunoprecipitation did not show lamin A/C sumoylation by Sumo1. Mass spectrometric analysis indicates that heterogeneous ribonucleoprotein U may be a novel lamin A/C binding partner that is sumoylated by Sumo1. In conclusion, I found that two cellular pathways are perturbed in the presence of LMNA mutations and might account for the specific symptoms observed in the tissue-specific laminopathies. Incorrect activation or deactivation of tissue-specific targets may lead to the wide range of tissue-specific diseases associated with LMNA mutations.
Keywords: Chemistry, Biochemistry.